Introduction. Architextures. Building, Writing, Speaking in Nordic Literatures and Languages - Meregalli, Andrea; Romanzi, Andrea; Storskog, Camilla (Folia Scandinavica Posnaniensia, 2025)
This special issue of Folia Scandinavica Posnaniensia, “Architextures. Building, Writing, Speaking in Nordic Literatures and Languages”, explores intersections of architecture, literature, and language. It investigates writerly responses to architectural styles, architecture as narrative settings, as a model for textual construction, and as metaphor for language structures. The contributions are grouped into three sections. The first section addresses the narrative potential of buildings and urban environments in the authorships of Hjalmar Bergman, Kjell Westö, Lotte Inuk, Mads Peder Nordbo, Simon Stålenhag, and Jonas Karlsson. The second considers textual structures as architectural forms, from saga archetypes to the organisation of Nordic svartebøker. The third focuses on the building blocks of language through studies on Old Icelandic word order and Swedish verbal polysemy. Through a variety of perspectives, this volume fosters new connections between space, structure, literary and linguistic discourses in Nordic studies.